Pengaruh Perceived Value Dan Kualitas Produk Terhadap Kepuasan Pelanggan Es Kristal Frostiq Di Maumere - Sady, Ignatius Raynaldo; Dekrita, Yosefina Andia; Dimas Realino (Jurnal Projemen UNIPA, 2026)
This study aims to analyze the influence of Perceived Value and product quality on customer satisfaction at Es Kristal Frostiq in Maumere. This study employs an explanatory quantitative approach with 110 customers of Es Kristal Frostiq as respondents, selected using purposive sampling. Data were collected through questionnaires, interviews, observation, and documentation. Data analysis used multiple linear regression complemented by validity, reliability, classical assumption tests, and hypothesis testing (t-test and F-test) using SPSS software. The results indicate that Perceived Value and product quality have a positive and significant effect on customer satisfaction, both partially and simultaneously (F-test sig. = 0.000 < 0.05). The coefficient of determination (R²) of 0.659 shows that both variables explain 65.9% of the variation in customer satisfaction. These findings imply that improving perceived value and product quality are key factors in strengthening customer satisfaction and the competitiveness of Es Kristal Frostiq in Maumere.